2013
DOI: 10.1063/1.4811474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two-temperature electrons distribution on an electrostatic plasma sheath

Abstract: A magnetized collisionless plasma sheath containing two-temperature electrons is studied using a one-dimensional model in which the low-temperature electrons are described by Maxwellian distribution (MD) and high-temperature electrons are described by truncated Maxwellian distribution (TMD). Based on the ion wave approach, a modified sheath criterion including effect of TMD caused by high-temperature electrons energy above the sheath potential energy is established theoretically. The model is also used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Electrons with v > v ch will get absorbed at the wall. Following the concept of cut off speed [17,21], the hot electron density distribution is given by…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Electrons with v > v ch will get absorbed at the wall. Following the concept of cut off speed [17,21], the hot electron density distribution is given by…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Thus, the IEDs can be expressed by. [5,9] f (E i0 ) = dN(E i0 )∕dE i0 (11) In our calculation, Equations (1) and (5)-(6) are solved through a second-order finite-difference scheme in space and an explicit scheme in time. With the plasma-sheath edge conditions n i,0 = n e,0 , (d s , t) = 0, and v i0 = C s , a set of closed non-linear equations for the sheath model and equivalent circuit model can be solved numerically by using an iteration method.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The presence of energetic electrons makes the electron distribution non-equilibrium and some deviation from the Maxwellian. Related to the problem of the sheath formation in non-stationary plasmas, some authors attempted to include the effects of a non-Maxwellian distribution function by the sum of two distributions consisting of a thermal Maxwellian background F I G U R E 1 The geometry of the radio frequency (RF) sheath model and the corresponding schematic diagram of the equivalent circuit for the RF sheath model and a small super-thermal population, [10][11][12] a q-non-extensive electron distribution, or Kappa distribution. [13][14][15][16] For plasmas described by a Kappa distribution, it has been shown [14] that the Debye length is always smaller than the shielding distance in a Maxwellian plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Since the forces acting on the dust particles and charging processes are important in characterization of the plasma sheath, numerous research studies investigated these effects and it was found that the presence of dust nanoparticles modifies the structure of the plasma sheath. [28][29][30] In this work, we use the Cairns et al [15] distribution for non-thermal electrons and investigate the effects of non-thermal electrons on the sheath structure. [15][16][17][18][19][20] At low-pressure discharges, the electron energy distribution departs significantly from the Maxwellian distribution and represents a non-thermal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Some other authors assumed two temperature electron distributions to study the effects of non-thermal electrons. [28][29][30] In this work, we use the Cairns et al [15] distribution for non-thermal electrons and investigate the effects of non-thermal electrons on the sheath structure. In recent years, this type of distribution function has been employed to investigate some basic physical characteristics of the plasmas such as dust acoustic waves, [31][32][33][34] ion acoustic waves, [35] magnetized electron-positron-ion plasma, [36] laser-created plasma, [37] electron acoustic solitary waves, [38] and dust charging.…”
Section: Introductionmentioning
confidence: 99%